2021
DOI: 10.1155/2021/9964143
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction, Saturated Fat Intake, and Body Mass Index in Peruvian Adults: A Cross-Sectional Survey

Abstract: Background. Cardiovascular diseases (CVDs) constitute one of the main public health problems and represent a greater risk of mortality and morbidity for the world population. The objective of the study was to determine food addiction, saturated fat intake, and body mass index (BMI) in Peruvian adults. Materials and Methods. A cross-sectional online survey was applied to 394 Peruvian adults over 18 years old residing in the three regions of the country. Participant data was collected through a prestructured onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…These results coincide with the findings of a previous study carried out in university students, in which it was found that men had greater excess body weight [ 25 ]. Similarly, other studies showed statistically significant differences in terms of obesity between men and women [ 16 , 26 , 27 ]. Epidemiological evidence available in Western countries shows an increasing trend of obesity in males than females [ 28 ].…”
Section: Discussionsupporting
confidence: 58%
“…These results coincide with the findings of a previous study carried out in university students, in which it was found that men had greater excess body weight [ 25 ]. Similarly, other studies showed statistically significant differences in terms of obesity between men and women [ 16 , 26 , 27 ]. Epidemiological evidence available in Western countries shows an increasing trend of obesity in males than females [ 28 ].…”
Section: Discussionsupporting
confidence: 58%
“…Another study reported that the risk of being overweight and obese was 3.8 times higher among male students [ 23 ]. Moreover, recent evidence from studies carried out in Peru shows that Peruvian men have a higher prevalence of overweight and obesity [ 24 ]. However, there are discrepancies with the findings reported by Soares and Barreto [ 25 ], who reported that Brazilian women are more overweight and obese than men, showing that they have 2.2 times the risk of being overweight or obese compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting a healthy lifestyle, including a plant-based diet with plenty of minimally processed plant foods such as fruits, vegetables, nuts, and whole grains 6 as well as the Mediterranean diet, with healthy foods such as fish and fermented or low-fat dairy products, may be beneficial in the prevention of NCDs. 7 In contrast, studies have shown that foods high in saturated fats, free sugars, and sodium represent a major risk factor for NCDs, including cardiovascular disease, 8 increased risk of overweight/obesity, 9 type 2 diabetes mellitus, dyslipidemia, 10 and different types of cancer. 11 In addition, other research has indicated that excessive consumption of high-calorie dense foods, characterized by being poor in beneficial nutrients such as dietary fiber, vitamins, minerals, complex carbohydrates and bioactive elements, is associated with a higher probability of all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%